Contribution to the Entailment Citizen - Hernández, Adolfo; González, Luis Armando (Qualitative and Quantitative Methods in Libraries, 2019)
Parliamentary libraries are embedded inside parliaments and the services provided are related to its role in supporting parliamentary work mainly, but these services are also used by society. The question arises of what worth they represent these services to the community that uses them and how to determinate the worth they bring parliamentary libraries to society. We propose a model that considers the use of the methods of the market prices assignment and contingent valuation to determine the social return in investment. This proposal was applied to a case study in the Library of the National Congress of Chile, to identify specific aspects of use and economic impact of the main associated services to the strategic objective of Entailment the National Congress with the Society, finally estimate the social return on investment. The result of this study shows an important difference between these two methods to determine the return for every dollar invested in the service, for assignment of market prices social return on investment was from USD 5.7 and for contingent valuation was USD 0.51. That difference is explained by the number of users who use the face-to-face services and the users who use only the services supported by the information technologies, due to the lack of knowledge of available services.